Influence of nanoemulsion/gum ratio on droplet size distribution, rheology and physical stability of nanoemulgels containing inulin and omega‐3 fatty acids. (31st May 2022) - Alfaro‐Rodríguez, María‐Carmen; Prieto, P.; García, M. C.; Martín‐Piñero, M. J.; Muñoz, J.
Abstract: Background: New consumer habits are forcing the food industry to develop new and healthy products. In response to this tendency, in this investigation, we obtained nanoemulgels by microfluidization containing inulin fibre and omega‐3 fatty acids. First, the influence of the number of microfluidization cycles on the physical properties of the nanoemulsions was studied. Subsequently, an advanced‐performance xanthan gum was added to the nanoemulsion in different nanoemulsion/xanthan ratios (1:1, 2:1, 3:1, 4:1, 1:2, and 1:3). Results: Laser diffraction, multiple light scattering, and rheology techniques were used to characterize nanoemulsions and the corresponding nanoemulgels. The nanoemulsion with the lowest Sauter mean diameter (138 nm) and the longest physical stability was obtained after three passes through a microfluidization device at a fixed pressure of 103 421 kPa. Thus, these processing conditions were always used to obtain the nanoemulsion; these were subsequently mixed with a xanthan gum solution to produce nanoemulgels that showed weak gel‐like viscoelastic and shear‐thinning flow behaviours. A decrease in the nanoemulsion/xanthan ratio (i.e. by an increase in the content of xanthan gum in the nanoemulgel) increased the viscoelastic moduli and the zero shear viscosity values. A rise in the droplet size was observed with aging time, probably due to flocculation. The nanoemulsion/xanthan gum mass ratio of 1:3 yielded the most stable nanoemulgel. Conclusions: This work is a contribution to the development of functional foods. It has been demonstrated that it is possible to obtain a stable nanoemulgel‐based food matrix containing fibre and omega‐3 fatty acids. © 2022 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.